Editorial - Morales Gutiérrez, Fredy (2021)
The Faculty of Education Sciences, is allowed to present number 19 of the Education Magazine, which through its content guides the analysis of the educational reality, both local, national and international, in a perspective of internationalization of the magazine, which allow its contents to be universalized, and that it is the means for the students, teachers and administrators of the Faculty to have the possibility of contributing to the global educational analysis, through the results of their research, both at the undergraduate and postgraduate level.